The effects of fatigue on instep kick performance in soccer - Bekir Mehtap; Sukru Balcı (Türk Spor ve Egzersiz Dergisi)
This study was applied to investigate the effects of fatigue on instep kick performance in soccer. Seven male soccer players participated in this research. Each had a minimum 6 years of soccer playing experience. The age was (mean±SD) 22.85 ± 1.57 years, height 178.14 ± 3.08 cm, weight 69.35 ± 3.71 kg, body mass index 21.86 ± 1.25 kg/m2 and maxVO2 values were 59.14 ± 4.77 ml/kg/min of subjects. The high intensity endurance protocol selected to be used in the present study has been previously applied to simulate soccer field conditions to occur fatigue on subjects. The subjects performed 5 instep kicks from the 16 m distance to the goal targets prior to, in the middle and after the implementation of a 90 min intermittent exercise protocol. Analysis of the sprint times taking a part in an exercise protocol, the significant difference was found (P lt;0.01). While there was an increase on sprint times, after the multiple comparison the significant difference was came out between the first and the last parts of the test protocol (P lt;0.05). During the exercise, when the average heart rate of subjects was compared according to the parts; there was significant differences with the first and third parts between the second and last parts (P lt;0.01). The lactate levels of subjects were increased throughout the exercise application. The results indicated that the lactate values were also significantly higher compared with the pre-fatigue values (P lt;0.01).  The decrease was occurred on instep kick performance performed in accordance with F-Marc shooting dead ball test of all subject in the middle and after of the exercise protocol. The present results suggest that the fatigue affects the soccer kick performance. While the kicks apart the parts was compared there is a significant decreasing was observed. It can say that the fatigue affects the success of the kick.